2011
DOI: 10.1007/s00572-011-0406-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal networks affect ectomycorrhizal fungal community similarity between conspecific trees and seedlings

Abstract: Ectomycorrhizal (EM) networks (MN) are thought to be an important mode of EM fungal colonization of coniferous seedlings. How MNs affect EM communities on seedlings, and how this varies with biotic and abiotic factors, is integral to understanding their importance in seedling establishment. We examined EM fungal community similarity between mature trees and conspecific interior Douglas-fir (Pseudotsuga menziesii var. glauca) seedlings in two experiments where seed and nursery-grown seedlings originating from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…There were little changes in seasonal dynamics and in response to drought in sebacinalean ECMs of a Mediterranean forest dominated by Quercus ilex (Richard et al 2011). ECM networks of adult Pseudotsuga menziesii seemed to be advantageous for their seedlings, especially under drought stress (Bingham and Simard 2012). The dominant OTUs of Pinus montezumae ECMs were composed of Atheliaceae, Cortinariaceae, and Sebacinaceae, but differed on seedlings and adult pines (Reverchon et al 2012).…”
Section: Sebacinalean Ectomycorrhizae (Ecm)mentioning
confidence: 97%
“…There were little changes in seasonal dynamics and in response to drought in sebacinalean ECMs of a Mediterranean forest dominated by Quercus ilex (Richard et al 2011). ECM networks of adult Pseudotsuga menziesii seemed to be advantageous for their seedlings, especially under drought stress (Bingham and Simard 2012). The dominant OTUs of Pinus montezumae ECMs were composed of Atheliaceae, Cortinariaceae, and Sebacinaceae, but differed on seedlings and adult pines (Reverchon et al 2012).…”
Section: Sebacinalean Ectomycorrhizae (Ecm)mentioning
confidence: 97%
“…Effects on soil invertebrates were not specifically investigated; however, Teste and others (2006) found that moisture equilibrated rapidly between soil inside and outside of mesh bags of both pore sizes. Old trees and seedlings shared eight fungal morphotypes over 60% of their root tips, indicating strong networking potential (Bingham and Simard 2011b). Mesh bags were 17 cm diameter by 32 cm deep, and completely encapsulated the root system of the seedling.…”
Section: Experimental Designmentioning
confidence: 99%
“…Soil moisture regimes refer to the average amount of soil water annually available for evapotranspiration by vascular plants over multiple years (Pojar, Klinka & Meidinger ). Recent field experiments have found that mycorrhizal network facilitation between mature and regenerating interior Douglas‐fir trees increases under water deficit conditions (Bingham & Simard ). These findings support the stress‐gradient hypothesis, which infers that net effects of community interactions shift in importance from competition to facilitation with increasing environmental stress (Bertness & Callaway ; Callaway ; Brooker et al .…”
Section: Introductionmentioning
confidence: 99%